Gastrointestinal stromal tumours: from KIT to succinate dehydrogenase. Issue 1 (28th November 2013) - Doyle, Leona A; Hornick, Jason L
<x xml:space="preserve">Abstract</x> The discovery of activating mutations in the tyrosine kinase receptor genes KIT and PDGFRA has led to the development of effective targeted therapies for gastrointestinal stromal tumours (GISTs). Specific genotypes, in part, predict the response to treatment with tyrosine kinase inhibitors. However, ~10% of GISTs lack such mutations (often referred to as 'wild‐type' GISTs). Recent insights into the biology of 'wild‐type' GISTs have resulted in clinically significant subclassification of this heterogeneous group of tumours, a large subset of which are now known to represent succinate dehydrogenase‐deficient GISTs. Recognition of this distinctive class of tumours has critical implications for prognosis, therapy, clinical follow‐up, and genetic counselling. Other uncommon genetic groups include neurofibromatosis type I‐associated and BRAF‐mutant GISTs. This review provides an update on the diagnosis and pathogenesis of these less common classes of GISTs, summarizes the clinical and pathological features associated with particular genotypes, and discusses mechanisms of resistance to targeted therapies.